Comparison of the Effects of Intralipid 10% and 20% on Peripheral Catheter Ablation in a Pediatric Intensive Care Unit - Farzaneh Mohammadi (Iranian Journal of Neonatology, 2016)
Background: Energy deficit is a common and serious problem in pediatric intensive care units. Parenteral nutrition, either alone or in combination with enteral nutrition, can improve nutrient delivery in critically ill patients by preventing or correcting the energy deficit and improving the outcomes. Intralipid 10% and 20% are lipid emulsions, widely used in parenteral nutrition. Despite several clinical advantages, intravenous Intralipid therapy has been associated with several complications.In this study, we aimed to investigate the effects of Intralipid 10% and 20% on peripheral intravenous catheter ablation in children receiving Intralipid in a pediatric intensive care unit. Methods: In this observational study, 96 patients were recruited through simple non-random sampling over six months. In total, 48 patients received intravenous Intralipid 10%, while 48 patients were administered Intralipid 20% as part of their parenteral nutrition plan. Through separate peripheral intravenous catheters, 0.5-3 g/kg/day of Intralipid was administered at an infusion rate of 0.5 g/kg/h. Length of hospital stay and intravenous catheter ablation were compared between the two groups. Results: Age of the patients ranged between two days and eight years. Esophageal atresia was the most common condition among patients receiving intravenous Intralipid infusion (8.3%). The mean duration of catheter survival was significantly shorter in patients receiving Intralipid 20% (28.77 vs. 68.23 h, P